Efikasi Diri Guru dan Efikasi Umum Guru dalam Pendidikan Karakter Ditinjau dari Latar Belakang Pendidikan dan Pengalaman Pelatihan - Shafa Nur Haryastutiningtyas; Ali Formen (Universitas Muhammadiyah Metro, 2025)
The importance of the role of teachers in character education requires a more in-depth review. To improve a teacher's ability to teach, a high level of efficacy is needed to believe that teachers can instill positive values. There are two efficacies in this study, namely Teacher Self-Efficacy (PTE) and Teacher General Efficacy (GTE). This article discusses teacher self-efficacy and teacher general efficacy in character education in terms of educational background and teacher training experience. The purpose of this research was to determine the effect of educational background and training experience on a teacher's PTE and GTE. This research method uses a quantitative approach method with data collection from 143 teachers as respondents using a questionnaire distributed to early childhood education teachers in Gajahmungkur District as research respondents. The questionnaire contains the aspects being studied. Respondent data is processed using the ANOVA method to obtain the results of the study. The results obtained in this study are that the educational background and training experience that have been obtained by teachers have significant results on teacher self-efficacy and teacher general efficacy. The findings of this study are that educational background and training experience have a significant influence on teacher self-efficacy. Therefore, teacher education institutions, especially PGPAUD and PIAUD study programs, need to improve the quality of teachers to be in line with educational needs in the field.